Do employee wellbeing and employee service performance affected with psychological stress post Covid 19? - Dato Mansor, Zuraina; Mohamed, Rosmah (Macrothink Institute, 2024)
Given the importance of employee service performance, this study aims to examine the relationship between stress factors and employee well-being, and test whether perceived organization support (POS) can leverage the effect of stress on employee service performance (ESP). Additionally, the study examines the mediating role of employee well-being (EWB) on the relationship between stress factors and ESP. The data were gathered using close-ended, self-administered five Likert scale questionnaires from frontline employees working in retail industries in Klang Valley, Malaysia, through google form surveys. A total of 276 data was collected. Hypotheses were developed based on Job Demand-Resource (JD-R) theory and tested using PLS-SEM technique. Results revealed that stress factors (emotional exhaustion and perceived job insecurity) are not significantly associated with EWB, but EWB significantly related to ESP. The result also shown that EWB does not mediate the relationship between stress factors and ESP, POS does not moderate the relationship between stress factors and EW. Instead of diminishing the stress factors (job demands: emotional exhaustion and perceived job insecurity) among the employees in retail industries, the study anticipated that by increasing the level of job resources, may influence the EWB and motivate a better ESP. The study extends the current literature on EWB by examining the effect of stress from the psychological perspective with the ESP by focusing on specifically on the influence of perceived job insecurity and emotional exhaustion to EWB.